PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI: STUDI PADA BIRO HUMAS DAN KSI BPK RI - Utama, Zahera Mega; Apriyana, Apriyana; Darmayanti, Ratna Tri; Aryani, Ricca Dwi (Jurnal Pijar, 2025)
This study aims to determine the influence of leadership style on employee performance at the Public Relations and International Cooperation Bureau of Audit Board of Indonesia (BPK RI). The research method used is quantitative method. The population in this study was all 92 employees of the Public Relations and International Cooperation Bureau at the BPK RI. The sample was selected using simple random sampling with the Slovin formula. The research instrument was tested for validity and reliability. Hypothesis testing used simple linear regression, correlation, and determination. The results of this study indicate that leadership style does not significantly influence employee performance at the BPK RI Public Relations and International Cooperation Bureau. Keywords: Leadership Style, Employee Performance